2016
DOI: 10.1038/cdd.2016.14
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3 regulates a non-canonical platform for caspase-8 activation during epithelial cell apoptosis

Abstract: Nod-like receptor, pyrin containing 3 (NLRP3) is characterized primarily as a canonical caspase-1 activating inflammasome in macrophages. NLRP3 is also expressed in the epithelium of the kidney and gut; however, its function remains largely undefined. Primary mouse tubular epithelial cells (TEC) lacking Nlrp3 displayed reduced apoptosis downstream of the tumor necrosis factor (TNF) receptor and CD95. TECs were identified as type II apoptotic cells that activated caspase-8, tBid and mitochondrial apoptosis via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
81
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(85 citation statements)
references
References 43 publications
3
81
0
1
Order By: Relevance
“…Alternatively, perhaps the HCV-induced apoptotic and pyroptotic pathways share a common origin that activates both of them. Interestingly, recent evidence suggests that in addition to their classical role in activating caspase-1 and inducing pyroptosis, NLRP3 inflammasomes can also activate caspase-8, which in turn induces apoptosis6970717273. This could be the case in HCV infection whereby activation of the NLRP3 inflammasome activates caspase-8 and caspase-1 to induce both apoptosis and pyroptosis, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, perhaps the HCV-induced apoptotic and pyroptotic pathways share a common origin that activates both of them. Interestingly, recent evidence suggests that in addition to their classical role in activating caspase-1 and inducing pyroptosis, NLRP3 inflammasomes can also activate caspase-8, which in turn induces apoptosis6970717273. This could be the case in HCV infection whereby activation of the NLRP3 inflammasome activates caspase-8 and caspase-1 to induce both apoptosis and pyroptosis, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…ASC has been reported to trigger Fas ligand-induced caspase-8-dependent apoptosis [30, 31], but reports on ASC and caspase-9 are few. McConnell et al [32] demonstrated that ASC (TMS1)-induced apoptosis proceeded through a CARD-dependent aggregation step followed by the activation of a caspase-9-mediated pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Caspase-8-mediated apoptosis is activated by the NLRC4 inflammasome through the interaction of SUG1 and FADD (95) and complex formation of NLRP3-ASC on mitochondria can activate caspase-8 in epithelial cells (96). In absence of caspase-1 in dendritic cells (97) or macrophages (98) inflammasomes can induce apoptosis, but in presence of caspase-1 and -11 inflammasomes can engage another form of programmed necrotic cell death; pyroptosis.…”
Section: Caspase-8 In Inflammasomesmentioning
confidence: 99%